Trade Controversy Amidst Tobacco Control Provisions: Dynamics on the Establishment of U.S Tobacco Control Act 2009 - Puguh Toko Arisanto (Parahyangan Center for International Studies, 2017)
AbstractThis article examines the dynamics on the establishment of a health policy that U.S suddenly issued, so-called Family Smoking Prevention and Tobacco Control Act (FSPTCA). Some provisions of this act having something to do with trade were assumed controversial policy due to two reasons. First, it banned the circulations of specific flavors in cigarettes but allowed menthol-containing tobacco products. Second, this act involved tobacco industry participation on Tobacco Products Scientific Advisory Committee (TPSAC). In short, this article addresses interest groups consisting of tobacco companies and civil society groups influencing U.S government to take action regarding ratification of World Health Organization Framework Convention on Tobacco Control (WHO FCTC). They both have contradicting interests and race against each other to influence government through varied means. I argue that this opposing domestic dynamics influences U.S government to issue FSPTCA that contained two controversies and adopted provisions of WHO FCTC as win-win solution. Keywords: tobacco control; interest groups; ratification; influence; win-win solution. AbstrakArtikel ini membahas mengenai dinamika pembentukan sebuah kebijakan atau undang-undang kesehatan Amerika, FSPTCA yang dikeluarkan secara mendadak. Beberapa ketentuan dari undang-undang ini berkaitan dengan perdagangan dan diasumsikan sebagai kebijakan yang kontroversial karena dua alasan. Pertama, undang-undang ini melarang peredaran rokok beraroma rasa namun mengizinkan produk tembakau yang mengandung mentol. Kedua, undang-undang ini melibatkan partisipasi industri tembakau dalam sebuah kelompok para penasehat ilmiah produk tembakau. Singkatnya, artikel ini merujuk pada kelompok kepentingan yaitu perusahaan-perusahaan rokok dan kelompok masyarakat sipil yang mempengaruhi pemerintah dalam meratifikasi konvensi kerangka kontrol tembakau dari WHO. Mereka memiliki kepentingan yang saling bertentangan dan saling berlomba untuk mempengaruhi pemerintah Amerika melalui berbagai macam cara. Akhirnya, penulis beragumen bahwa dinamika domestik yang saling bertentangan mempengaruhi pemerintah AS untuk mengeluarkan kebijakan FSPTCA yang memuat dua kontroversi dan mengadopsi ketentuan WHO FCTC dengan dua kontroversinya sebagai win-win solution. Kata Kunci: kontrol tembakau; kelompok kepentingan; ratifikasi; mempengaruhi; win-win solution.